2023
DOI: 10.1002/esp.5666
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling fluvial versus glacial legacy controls on boulder‐bed river geomorphology for semi‐alluvial rivers in Fennoscandia

Richard J. Mason,
Lina E. Polvi

Abstract: River management is founded on predictable self‐organisation between river form and catchment controls in alluvial rivers. However, a substantial proportion of rivers are not fully alluvial. In previously glaciated landscapes, boulder‐rich glacial till influences river channel form and process. Increasing interest in nature‐ and process‐based river restoration requires knowledge of pre‐disturbance natural processes, which does not exist for semi‐ and non‐alluvial rivers in Fennoscandia. We aimed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 85 publications
(167 reference statements)
1
14
0
Order By: Relevance
“…This study extends the analysis of field data collected to understand the controls on boulder-bed channel morphology in previously glaciated catchments in northern Sweden (Mason & Polvi, 2023). In these catchments, glacial legacies influence both valley geometry and reachscale channel morphology via glacial legacy sediments in the form of large boulders (Figure 1).…”
Section: Methodssupporting
confidence: 56%
See 4 more Smart Citations
“…This study extends the analysis of field data collected to understand the controls on boulder-bed channel morphology in previously glaciated catchments in northern Sweden (Mason & Polvi, 2023). In these catchments, glacial legacies influence both valley geometry and reachscale channel morphology via glacial legacy sediments in the form of large boulders (Figure 1).…”
Section: Methodssupporting
confidence: 56%
“…They found limited evidence of alluvial processes and concluded that channel geometry and boulder characteristics were derived from legacy glacial processes, with little modification by contemporary fluvial processes (Mason & Polvi, 2023). We repeat this analysis with different definitions of boulder size.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations